Supporting agri-food projects to implement climate change adaptation through the interactive online tool ‘CRISP’ - Below, Till; Gassen, Alina; Voss, Maike; Bonilla Findji, Osana; Cramer, Laura K.; Gitau, Kevin; Gosling, Amanda; Pittore, Massimiliano; Renner, Kathrin; Zebisch, Marc; Corcoglioniti, Francesco; Mosca, Alessandro (2023)
Introduction International agri-food system programmes are increasingly seeking to mainstream climate action across their portfolios. A range of methods and tools exists, but there is no “ready-to-use” tool that allows a cost- and time-effective climate risk assessment for specific agri-food systems and the development of adaptation hypotheses. The Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ), with Eurac Research and the Alliance of Bioversity International and the International Centre for Tropical Agriculture (CIAT), set out to provide an easy-to-use tool that considers the specific characteristics of agri-food systems under a changing climate.